Venous Malformation Leading To Pelvic Congestion Syndrome: A Case Report - Che Ros, Mohamad Izzat Arslan; Zakaria, Rozman (The Interventionalist Journal, 2023)
Pelvic congestion syndrome (PCS) is a chronic condition that mainly affects female. We report a case of long-standing chronic lower abdominal pain caused by pelvic congestion syndrome, which is often underdiagnosed, and discuss the imaging findings. The patient was treated endovascularly with an IUD and lipiodol glue